A Rare Cause of Stroke in Young Adults: Occlusion of the Middle Cerebral Artery by a Meningioma Postpartum - Stéphane Mathis; Benoît Bataille; Samy Boucebci; Marion Jeantet; Jonathan Ciron; Laurène Vandamme; Jean-Philippe Neau (Case Reports in Neurological Medicine)
Meningioma is the most common nonglial intracranial primary tumor. It is a slowly growing tumor and presents clinically by causing seizures along with neurological or neuropsychological deficit. However, acute presentation of meningioma is possible. We are reporting a case of cerebral infarction due to a sphenoid wing meningothelial meningioma (with progesterone receptor positivity) leading to an occlusion of the middle cerebral artery (MCA) in a 30-year-old right-handed woman (1 month after childbirth). After surgery, no new neurological event occurred, and she recovered most of her neurological functions. Strokes due to meningioma are a highly rare clinical occurrence but should be given serious consideration, particularly in young patients.